Clinical characteristics and treatment modalities in uremic and non uremic calciphylaxis - a dermatological single-center experience - Sabine Yousuf; Dorothee Busch; Regina Renner; Stefan Schliep; Cornelia Erfurt-Berge (Renal Failure)
Calciphylaxis (CP) is a serious, potentially life-threatening disease that presents with medial calcification of small-sized vessels and painful ischemic ulcerations. Although calciphylaxis is frequently seen in patients with end-stage kidney disease on dialysis (calcific uremic arteriolopathy, CUA), there are reported cases of nonuremic calciphylaxis (NUC), which often remain undiagnosed. We conducted a retrospective chart review at our dermatological hospital and evaluated data concerning the epidemiology, comorbidities, medication, laboratory abnormalities, and therapeutic approaches of 60 patients diagnosed with calciphylaxis between 01/2012 and 12/2022. We identified 21 patients diagnosed with NUC and 39 with kidney disease. The predilection sites of skin lesions were the lower legs in 88% (n = 53), followed by the thigh and gluteal regions in 7% (n = 4). Significant differences were identified in comorbidities, such as atrial fibrillation (p < 0.001) and hyperparathyroidism (p < 0.01) accounting for CUA patients. Medication with vitamin K antagonists (p < 0.001), phosphate binders (p < 0.001), and loop diuretics (p < 0.01) was found to be associated with the onset of calciphylaxis. Hyperphosphatemia (p < 0.001), increased parathyroid hormone (p < 0.01) and triglyceride levels (p < 0.01), hypoalbuminemia (p < 0.01) and decreased hemoglobin values (p < 0.001) in the CUA cohort were significantly different from those in the NUC group. All patients with CUA received systemic medication. In contrast, only 38% (n = 8) of patients with NUC received systemic treatment. Striking discrepancies in the treatment of both cohorts were detected. In particular, NUC remains a disease pattern that is still poorly understood and differs from CUA in several important parameters.